Elucidating optimal exhaust manifold divergence and temperature distribution in improving low-end engine speed performance - Ramasamy, Girrimuniswar; Mohamad Razlan, Zuradzman; Abu Bakar, Shahriman; Rojan, Mohammad Afendi; Ishak, Azizul Aziz; Rani, Muhammad Faiz Hilmi; Guan, Ng Yee; Murali, Rishan; Sunan, Sukport; Akbar Ali, Muhammad Hussein (Semarak Ilmu Publishing, 2024)
The exhaust manifold plays a crucial role in optimizing the performance of Spark-Ignition (SI) engines by effectively expelling combustion products. This study focuses on the optimization of the exhaust manifold design and temperature distribution in a 115-cc single-cylinder SI engine. The objective is to investigate the association between the design characteristics of the exhaust manifold, particularly its divergence, and the engine's performance in terms of brake power. Using computer-aided design (CAD), a three-dimensional model of the exhaust manifold with reduced diameter was developed. The optimized design aimed to enhance the engine's overall performance by achieving lower temperatures, particularly at low-end speeds. Subsequently, a 1D engine study was conducted to evaluate the performance of the engine with the optimized exhaust manifold design and validate the improved temperature distribution. The results demonstrate that the optimized exhaust manifold design leads to higher brake power while maintaining lower temperatures, especially at low-end speeds. This highlights the importance of exhaust manifold optimization and temperature distribution in maximizing the efficiency of the selected SI engine. To further enhance the engine's performance, future research should focus on identifying the most appropriate value for the exhaust manifold's divergence. This will contribute to the ongoing development of more efficient and high-performance SI engines. The findings of this study provide valuable insights into the optimization of exhaust manifold design and temperature distribution for improved engine performance in the context of the tested engine.